2015
DOI: 10.1038/nphys3325
|View full text |Cite
|
Sign up to set email alerts
|

Optically reconfigurable magnetic materials

Abstract: Structuring of materials is the most general approach for controlling waves in solids. As spin waves-eigen-excitations of the electrons' spin system-are free from Joule heating, they are of interest for a range of applications, such as processing 1-5 , filtering 6-8 and short-time data storage 9 . Whereas all these applications rely on predefined constant structures, a dynamic variation of the structures would provide additional, novel applications. Here, we present an approach for producing fully tunable, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
140
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(144 citation statements)
references
References 35 publications
(38 reference statements)
1
140
0
3
Order By: Relevance
“…15,16 In addition, MCs, in particular one-dimensional systems, possess the possibility of reprogramming the magnonic properties by a switching between different states in the magnetic hysteresis. [17][18][19][20][21][22] In previous studies, it was already shown that MCs can be used as grating couplers, 23 for magnonic logic, [24][25][26][27] filter 28 and sensor 29 applications, and moreover, as a tool to access important material properties, such as the exchange constant, at high precision.…”
Section: 9-14mentioning
confidence: 99%
“…15,16 In addition, MCs, in particular one-dimensional systems, possess the possibility of reprogramming the magnonic properties by a switching between different states in the magnetic hysteresis. [17][18][19][20][21][22] In previous studies, it was already shown that MCs can be used as grating couplers, 23 for magnonic logic, [24][25][26][27] filter 28 and sensor 29 applications, and moreover, as a tool to access important material properties, such as the exchange constant, at high precision.…”
Section: 9-14mentioning
confidence: 99%
“…As spin waves, the collective precessional motion of localized electron spins, do not involve the motion of electrons, magnonic devices avoid Joule heating and thus allow low-power computing [36,38,46,47]. Moreover, their wave properties provide distinct functionalities [49][50][51][52][53] such as multi-input/output (nonlinear) operations [54,55]. Despite their attractive features, however, magnonic devices suffer from a small on/off ratio of spin-wave signal.…”
Section: Introductionmentioning
confidence: 99%
“…A paradigm that is the focus of recent investigation consists of actively modifying the band structure of magnonic crystals [15]. This has been achieved to date by use of Meander-type structures [16] and, more recently, via heating [17] in one-dimensional ferromagnets.…”
Section: Introductionmentioning
confidence: 99%